Komparasi Faktor Fundamental Mikro dan Makro Ekonomi in Jakarta Islamic Index dan Lq-45 - Zelivieska Bintang Maharani (Jurnal Ilmiah Ekonomi Islam, 2021)
The capital market in Indonesia has developed rapidly in line with the entry of the Islamic capital market. On the Indonesia Stock Exchange, there are Islamic and conventional stocks. In this study, the object of research is the Jakarta Islamic Index and LQ-45 stocks in 2015-2017. The purpose of this research is to compare the fundamental micro and macroeconomic factors and their effects on stock prices and stock returns. In selecting the sample, this study used a purposive sampling method, where the number of samples in this study were 15 companies Jakarta Islamic index and 13 companies LQ-45. The test uses the analysis technique of Structural Equation Modeling (SEM) to see how much influence the variables have and the comparison test with the Mann Whitney test. The results of this study indicate that only microeconomic factors have a significant effect on stock prices in the Jakarta Islamic index and LQ-45. The results also show that there is a significant difference between the micro-fundamental factors in the Jakarta Islamic index and LQ-45. Meanwhile, there is no significant difference in macro factors. Keywords: Micro Economy, Macro Economy, Stock Price, Stock Return